The Economic and political aftermath of the Arab Spring : perspectives from Middle East and North African Countries - Altomonte, Carlo; Ferrara, Massimiliano (Cheltenham Edward Elgar Publishing Ltd., 2014)
From Edward Elgar Publishing website: "The economies of the Middle East and North Africa (MENA) region have always been characterized by economic volatility and social disparities. The recent 'Arab Spring' wave of protests has increased political uncertainty and instability in the region, and this timely book provides an in-depth analysis of the subsequent changes from economic, political and environmental perspectives. The international contributors provide a comprehensive overview of the situation in the Mediterranean Basin, addressing a wide range of contributing factors including: - productivity and innovation - trade and foreign investment - changing geo-political equilibria - labour markets and the role of women- the environment, climate change and energy sourcing."
MENA countries : economic and political perspectives in the aftermath of the arab spring - an introduction / Carlo Altomonte and Massimiliano Ferrara -- 1. Gulf monarchies' role in the new MENA region / Valeria Talbot -- 2. Does MENA trade too little, both within the region and with other regions? If so, why, and if not, why not? / Arian Farshbaf and Jeffrey B. Nugent -- 3. Employment creation through inward FDI in the EMFTA and employment linkages within sectors / Sergio Alessandrini -- 4. International trade, female labor and enterpreneurship in MENA countries / Silvio Contessi, Francesca de Nicola and Li Li -- 5. Climalte change challenges and policies for the MENA countries / Ali H. Bayar and Hoda Youssef -- 6. The energy sector in Mediterranean and MENA countries / Marcella Nicolini and Simona Porcheri -- 7. Innovation performance of MENA countries : where do we stand? / Maria Giovanna Basco and Roberto Mavilia --
Includes bibliographical references and index
Keywords: Economic conditions; ECONOMIC CONDITIONS; POLITICAL CONDITIONS; GOVERNMENT POLICY; PROTEST MOVEMENTS; ARAB COUNTRIES; NORTH AFRICA; MIDDLE EAST